Optimizing Innovative Learning Strategies to Improve Elementary School Students' Learning Outcomes: A Literature Review - Rosmaria Rosmaria (PT. Anagata Sembagi Education, 2024)
Improving the quality of elementary school student learning outcomes is a top priority in basic education development. Various studies indicate that low academic achievement and lack of active student engagement in the learning process are influenced by conventional learning approaches. This study aims to examine in depth the effectiveness of innovative learning strategies in improving elementary school student learning outcomes through a qualitative literature study method. Data were obtained from various scientific sources such as national and international journals, conference proceedings, and research reports from the last five years (2020–2025). The analysis was conducted using content analysis techniques with a thematic approach. The study results indicate that learning strategies such as Project-Based Learning, Inquiry-Based Learning, Flipped Classroom, and technology integration such as Augmented Reality consistently have a positive impact on student motivation, conceptual understanding, and critical thinking skills. However, the effectiveness of these strategies is greatly influenced by teacher readiness, institutional support, and the availability of educational infrastructure. This study recommends the importance of evidence-based pedagogical literacy and strengthening teacher capacity as efforts to optimize innovative learning. This study is expected to serve as a conceptual and practical reference for educators, researchers, and policymakers in designing transformative learning at the elementary school level.